Validation of a micromethod for quantification of lutein and beta-carotene in olive oil - Lúcia Maia (2008)
A micromethod was developed and validated for the quantification of lutein and beta-carotene in olive oils. The compounds are liquid-liquid extracted with n-hexane and n,n-dimethylformamide (DMF), by vortex mixing and centrifugation. The n-hexane phase retains beta-carotene, whereas the DMF phase retains lutein. This last fraction is concentrated and analyzed by RP-HPLC/diode-array, with a gradient of acetonitrile, water, and ethyl acetate, using beta-apo-8'-carotenal as I.S. beta-carotene is quantified by UV/Vis measurements at 454nm, by the external standard method. The method shows appropriate inter- and intra-day reproducibility, accuracy, and linearity for both compounds, allowing fast analysis of several samples simultaneously, with a relatively small consumption of organic solvents. The analytical methodology was applied to several samples of commercial Portuguese PDO olive oils.